Spatial Suitability of Harvesting Floodwater in The King Suleiman bin Abdelaziz’s Royal Reserve by Using GIS: Wadi Tawarn as a Model - Aid, Norah Mashaan; Ahmed, Ummhani Idris (Journal of agricultural, environmental and veterinary sciences, 2025)
The present study aimed to delineate the optimal sites for water harvesting in Wadi Tuwaran, located within the King Salman bin Abdulaziz Royal Reserve, through the application of Geographic Information Systems (GIS) and the Analytic Hierarchy Process (AHP). A comprehensive spatial database was constructed for the wadi, which encompasses an area of (136.74) km² and receives an average annual rainfall of (168.47) mm. The terrain is characterized by its ruggedness, while the geological formations predominantly consist of resistant granitic rocks. The selection of evaluation criteria was guided by the standards of the Food and Agriculture Organization (FAO) in conjunction with insights from previous research. These criteria were subsequently analyzed, reclassified, and weighted based on expert judgments obtained through a structured questionnaire distributed to specialists across hydrology, geomorphology, climatology, and GIS. The analytical process yielded spatial suitability maps for both dams and ponds, revealing that the proportion of areas classified as highly suitable amounted to (0.37%) for dams and (1.46%) for ponds.